Curcumin Electrochemistry-Antioxidant Activity Assessment, Voltammetric Behavior and Quantitative Determination, Applications as Electrode Modifier - Iulia Gabriela David; Emilia Elena Iorgulescu; Dana Elena Popa; Mihaela Buleandra; Mihaela Carmen Cheregi; Hassan Noor (MDPI AG, 2023)
Curcumin (CU) is a polyphenolic compound extracted from turmeric, a well-known dietary spice. Since it has been shown that CU exerts beneficial effects on human health, interest has increased in its use but also in its analysis in different matrices. CU has an antioxidant character and is electroactive due to the presence of phenolic groups in its molecule. This paper reviews the data reported in the literature regarding the use of electrochemical techniques for the assessment of CU antioxidant activity and the investigation of the voltammetric behavior at different electrodes of free or loaded CU on various carriers. The performance characteristics and the analytical applications of the electrochemical methods developed for CU analysis are compared and critically discussed. Examples of voltammetric investigations of CU interaction with different metallic ions or of CU or CU complexes with DNA as well as the CU applications as electrode modifiers for the enhanced detection of various chemical species are also shown.